2019
DOI: 10.1007/s11892-019-1261-z
|View full text |Cite
|
Sign up to set email alerts
|

Organoids from the Human Fetal and Adult Pancreas

Abstract: Purpose of ReviewNovel 3D organoid culture techniques have enabled long-term expansion of pancreatic tissue. This review comprehensively summarizes and evaluates the applications of primary tissue–derived pancreatic organoids in regenerative studies, disease modelling, and personalized medicine.Recent FindingsOrganoids derived from human fetal and adult pancreatic tissue have been used to study pancreas development and repair. Generated adult human pancreatic organoids harbor the capacity for clonal expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 98 publications
(91 reference statements)
1
23
0
Order By: Relevance
“…Organoids can have clinical implications as they mimic patient response and can be used to identify patients that would benefit from certain treatments ( Tiriac et al, 2018 ). Additionally, organoids derived from embryonic pancreatic cells can also contribute to understanding better the human pancreatic development and lineage relationships, which are altered in PDAC ( Balak et al, 2019 ). Finally, organoid cultures can be established and propagated (albeit for a limited time) from adult pancreatic exocrine cells, which allows evaluating the contribution of individual genes and their influence on the PDAC tumorigenic process by the stepwise introduction of genetic alterations through genome editing approaches ( Figure 3B ) ( Greggio et al, 2013 ; Huch et al, 2013 ; Huch and Koo, 2015 ; Baker et al, 2016 ).…”
Section: Organoids: a 3d Platform To Model Pdac Initiation And Progressionmentioning
confidence: 99%
“…Organoids can have clinical implications as they mimic patient response and can be used to identify patients that would benefit from certain treatments ( Tiriac et al, 2018 ). Additionally, organoids derived from embryonic pancreatic cells can also contribute to understanding better the human pancreatic development and lineage relationships, which are altered in PDAC ( Balak et al, 2019 ). Finally, organoid cultures can be established and propagated (albeit for a limited time) from adult pancreatic exocrine cells, which allows evaluating the contribution of individual genes and their influence on the PDAC tumorigenic process by the stepwise introduction of genetic alterations through genome editing approaches ( Figure 3B ) ( Greggio et al, 2013 ; Huch et al, 2013 ; Huch and Koo, 2015 ; Baker et al, 2016 ).…”
Section: Organoids: a 3d Platform To Model Pdac Initiation And Progressionmentioning
confidence: 99%
“…Because PTOs can routinely be obtained from normal human epithelia, mutational processes during different phases of malignancy can be monitored in vitro, and in vitro culture of a range of premalignant pancreas neoplasias is now feasible [ 27 ]. However, PTOs do not rely on the R-spondin protein to activate Wnt pathway mutations, and their dependence on other niche growth factors is specifically lost in the adenoma-to-carcinoma transition [ 32 , 45 , 54 ]. Another relevant application of PTOs is their use in xenografts [ 55 , 56 ].…”
Section: Applications Of Ptosmentioning
confidence: 99%
“…PTOs constitute a tool for rapid drug assessment of individual tumors before or in parallel to implementing treatment in patients with PDAC [ 92 , 93 ]. Although a one-week time period between biopsy and drug selection has been reported, more recent studies have suggested that extensive drug screening should be performed within 3–4 weeks post-biopsy [ 45 , 60 , 94 ]. This technique can potentially reveal individual treatment vulnerabilities according to the genetic mutation profile and therapeutic response in organoids or determine the next lines of therapy in case of ineffective first-line treatment [ 95 , 96 ].…”
Section: Applications Of Ptosmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cell engineering has made it possible to develop functional β cell differentiation and representative 3D stem-cell-derived tissues, called organoids, to recreate critical functions of native pancreatic tissue in vitro [10][11][12][13][14][15][16][17][18] . Millman et al succeeded in generating stem-cell-derived β cells from diabetic patients, and they suggested that this approach might be an attractive candidate for patient-specific treatment, drug screening platform, and improvement of β cell biology 13 .…”
Section: Introductionmentioning
confidence: 99%